Evaluation of Repository Usability Test Using Nielsen'S Attributes of Usability (NAU) Model in Libraries - Miranti, Dwi; Sudiar, Nining; Latiar, Hadira (JIPI (Jurnal Ilmu Perpustakaan dan Informasi), 2024)
This research amis to evaluate the usability test repository using the Nielsen’s Attributes of Usability (NAU) model in the Muhammadiyah University of Riau Library. This type of research is descriptive with a quantitative approach. Data collection techniques were carried out by carrying out observations, distributif questionnaires, interviews and documentation.the sampel in this study amounted to 95 people from the total population. The results of this research found that the learnability indikator (user’s ease in learning/understanding smartlib) had an average value of 4,49. Efficiency indikator (user needs can be resolved accurately and completely using smartlib) with an average value of 4,42. Memorability indikator (user’s ease in remembering the smartlib system) with an average value of 4,44. The errors indikator (failure in smartlib) has an average value of 4,45, so failures can be found in the system. For this reason, there needs to be improvements in overcoming failure problems that are often found in smartlib, namely access speed, so that access failures can be reduced. Satisfaction indikator (user satisfaction with smartlib) with an average value of 4,42. Thus, it can be concluded that the usability test repository using the Nielsen’s Attributes of Usability (NAU) Model in the Smartlib Library of the Muhammadiyah University of Riau isi n the very good category with an average of 4,44 (88,8%).